Adsorção de contaminantes de biodiesel sobre fibras de bagaço modificadas em sua superfície - Oliveira, Renata de Souza (2017)
The sugarcane bagasse fibers, chemically modified on their surface, were used to adsorb biodiesel contaminants from soybean oil. Two biodiesel samples were used as adsorbents, crude biodiesel and washed. The contaminants present were mainly glycerol and water, but also ions and methanol. Washing biodiesel with distilled water removes most of the contaminants, however, adding large amounts of water, being difficult to remove because of the hydrophilic character of biodiesel as a hydrogen bond acceptor. The adsorbent used in this work showed to be very efficient for the removal of the contaminants of the crude biodiesel, and also, in the removal of water from the washed biodiesel. The adsorbed contaminants of the biodiesel were determined by thermal analysis (DSC and DTA) in the fibers (adsorbent) and biodiesel (adsorvato), comparing the results with the pure biodiesel. The percentage of free glycerol in the crude biodiesel showed a great reduction, showing the adsorption efficiency in this biodiesel sample, being estimated based on DSC glycerol signal area data a total amount of 1.34 g of fibers for its complete removal. The mass of bagasse fibers added (0.00 g to 1.00 g) in a fixed volume of biodiesel (10.00 mL) was a relevant parameter where the saturation of the fibers started around 0.70 g removing about 98 % glycerol and water.